Proposed diagnostic and prognostic markers of primary malignant hepatic vascular neoplasms - Youngeun Yoo; Jinho Shin; Eunsung Jun; Eun-Young Koh; Hwa Jeong Shin; Hyo Jeong Kang (BMC, 2024)
Abstract Introduction Primary malignant hepatic vascular tumors with various malignant potentials include epithelioid hemangioendothelioma (EHE) and angiosarcoma (AS), which may overlap pathologically. This study aimed to compare the pathological findings of hepatic EHE with those of AS, in association with patient outcomes. Methods Fifty-nine histologically confirmed patients with 34 EHE and 25 AS were admitted to a tertiary hospital from 2003 to 2020. Their EHE and AS pathological features were compared. Immunohistochemistry for CD31, ERG, CAMTA-1, TFE3, P53, and Ki-67 labeling was performed on paraffin-embedded blocks. Markers, along with histological findings, were analyzed for the purposes of diagnostic and prognostic significance by multivariate analysis. Results CAMTA-1 was 91.2% positive in EHE, but negative in AS (p = < 0.001). AS was significantly correlated to an aberrant p53 expression, high Ki-67 labeling, and high mitotic activity, compared to EHE (all, p = < 0.001). EHE can be classified as low grade (LG) and high grade (HG) using the prognostic values of mitotic activity and ki-67 labeling (sensitivity = 1, specificity = 1). Low grade-EHE showed significantly better overall survival than high grade-EHE (p = 0.020). Conclusions Immunohistochemistry for CAMTA-1, P53, and Ki-67 labeling may help distinguish EHE and AS in histologically ambiguous cases, especially small biopsied tissue. Moreover, the combination of mitotic activity and Ki-67 labeling can be a prognostic factor for EHE with various clinical features.